PENGARUH TREND FASHION DAN IMPULSE BUYING TERHADAP KEPUTUSAN PEMBELIAN DI HONGKONG FASHION JL. SISINGAMANGA RAJA SUDIREJO II, KEC. MEDAN KOTA - Sarinah Br Hasibuan; Rukmini; Muhammad Hilman Fikri; Zamaluddin Sembiring (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
This study aims to identify the impact of fashion trends and impulse buying on consumers' purchasing decisions at Hongkong Fashion, located on Sisingamangaraja Street, Sudirejo II Subdistrict, Medan Kota District. The background of this research stems from the growing phenomenon of consumer behavior in urban communities, particularly among the younger generation, who are often influenced by trends and temporary emotions when purchasing fashion products. The research method applied is quantitative with an associative approach. Data collection was carried out by distributing questionnaires to 93 respondents. Data analysis was conducted using multiple linear regression, including validity and reliability tests, classical assumption tests, t-test (partial), F-test (simultaneous), and coefficient of determination (R²) analysis. The results indicate that the impulse buying variable has a positive and significant effect on purchasing decisions, while the fashion trend variable has a negative but also significant influence. Both variables simultaneously have a significant impact on purchasing decisions, contributing 93.9%. These findings suggest that consumer buying behavior is more influenced by emotional drives and sudden desires than by understanding fashion trends. Therefore, companies are advised to enhance marketing strategies that focus on visual and emotional elements to stimulate impulsive purchases, while still presenting trends that align with the local consumers’ characteristics.